Patients' Experiences of Remote Neurology Consultations during the COVID-19 Pandemic - McKenna, Mary Clare (Eur Neurol, 2020)
Telemedicine has been widely implemented during the COVID-19 global pandemic to enable continuity of care of chronic illnesses. We modified our general neurology clinic to be conducted using remote audio-only telephone consultations. We included all patients over a 10-week period who agreed to both a telephone consultation and a questionnaire afterwards in order to ascertain the patient's perspective of the experience. There were 212 participants consisting of men (43.8%) and women (56.2%). The mean ± standard deviation of age was 47.8 ± 17.0 (range 17–93) years. For the most part, patients found remote consultations either “just as good” (67.1%) or “better” (9.0%) than face-to-face consultations. Those who deemed it to be “not as good” were significantly older (52.3 ± 17.9 years vs. 46.6 ± 16.6 years, p =0.045) or were more likely to have a neurological disorder that required clinical examination, namely, a neuromuscular condition (66.7%, p = 0.002) or an undiagnosed condition (46.7%, p = 0.031). At the height of the COVID-19 global pandemic, most patients were satisfied with remote consultations. The positive feedback for remote consultations needs to be verified outside of this unique scenario because the results were likely influenced by the patients' apprehension to attend the hospital amongst other factors.